2017
DOI: 10.1108/jsit-10-2016-0061
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of supervised machine learning techniques for customer churn prediction based on analysis of customer behavior

Abstract: Purpose This paper aims to provide a predictive framework of customer churn through six stages for accurate prediction and preventing customer churn in the field of business. Design/methodology/approach The six stages are as follows: first, collection of customer behavioral data and preparation of the data; second, the formation of derived variables and selection of influential variables, using a method of discriminant analysis; third, selection of training and testing data and reviewing their proportion; fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 55 publications
0
36
0
1
Order By: Relevance
“…Churn management emphasizes the need for banks to take steps to prevent or minimize customer churn through several customer retention programs [14]. This also helps to establish long-term relationships with customers and maximize the value of their customer base [15].…”
Section: Churn Management In the Banking Sectormentioning
confidence: 99%
“…Churn management emphasizes the need for banks to take steps to prevent or minimize customer churn through several customer retention programs [14]. This also helps to establish long-term relationships with customers and maximize the value of their customer base [15].…”
Section: Churn Management In the Banking Sectormentioning
confidence: 99%
“…Increasing the number of customers but experiencing the high churn of customers is the same as pouring water into leaking bucket [2]. Some churn definition that may different for each industry [3].…”
Section: B Churnmentioning
confidence: 99%
“…It is realized when we receive email, SMS and even chat which has been personalized but does not talk to use when we browse in a website and there is a banner of advertisement which is not suitable with our need. It may show us that profile, modelling and segmentation have not been done [3].…”
Section: Marketing Intelligencementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, study showed 1-4% performance improvement in the boosted versions. In [68] the study investigated the accuracy of different models (Multi-layer perceptron (MLP) and Decision Tree (C5)). The study showed that MLP achieves accuracy of 95.51%, which outperforms C5 decision tree 89.63%.…”
Section: ) Customer Developmentmentioning
confidence: 99%